2019
DOI: 10.1063/1.5080334
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol confined in zeolitic imidazolate frameworks: The temperature-dependent cooperativity length scale of glassy freezing

Abstract: In the present work, we employ broadband dielectric spectroscopy to study the molecular dynamics of the prototypical glass former glycerol confined in two microporous zeolitic imidazolate frameworks (ZIF-8 and ZIF-11) with well-defined pore diameters of 1.16 and 1.46 nm, respectively.The spectra reveal information on the modified  relaxation of the confined supercooled liquid, whose temperature dependence exhibits clear deviations from the typical super-Arrhenius temperature dependence of the bulk material, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 73 publications
3
44
0
Order By: Relevance
“…One can recall that this deviation occurring at T g,interfacial has been rationalized in terms of, i.e., the limited length scale of dynamic cooperativity of molecular motions, 67,68 or the vitrification of molecules strongly interacting with the interface (the interfacial layer). 62 Although the results obtained previously for glycerol infiltrated in metal−organic frameworks (MOF) supported the first hypothesis, 69,70 there are many reports, also coming from our group, confirming the latter explanation that was validated based on the combined dielectric and calorimetric investigations. Note that the data collected for various glass formers infiltrated into AAO templates of different d revealed that the deviation of τ α (T)dependences occurring at T g,interfacial corresponds well with the calorimetric high glass transition temperature recorded in thermograms.…”
Section: Resultssupporting
confidence: 77%
“…One can recall that this deviation occurring at T g,interfacial has been rationalized in terms of, i.e., the limited length scale of dynamic cooperativity of molecular motions, 67,68 or the vitrification of molecules strongly interacting with the interface (the interfacial layer). 62 Although the results obtained previously for glycerol infiltrated in metal−organic frameworks (MOF) supported the first hypothesis, 69,70 there are many reports, also coming from our group, confirming the latter explanation that was validated based on the combined dielectric and calorimetric investigations. Note that the data collected for various glass formers infiltrated into AAO templates of different d revealed that the deviation of τ α (T)dependences occurring at T g,interfacial corresponds well with the calorimetric high glass transition temperature recorded in thermograms.…”
Section: Resultssupporting
confidence: 77%
“…Using hosts with different pore diameters then can provide information about the temperature-dependent cooperativity length. 11 Therefore it seems natural to explain our results in confined water in the same way: Process 3 is the  relaxation of confined supercooled water (however, differing significantly from bulk water as discussed below) with T g  159 K. With decreasing temperature, at T cr  175 K its cooperativity length has grown to about 1.9 nm and, without confinement, would exceed the pore size under further cooling. Below T cr , the detected relaxation still reflects cooperative  dynamics, but with temperature-independent cooperativity because  is limited by the pore diameter d.…”
Section: Discussionmentioning
confidence: 72%
“…Such behavior is often found in supercooled liquids and can be used to estimate the size of the cooperativity length scale in dependence of temperature (see, e.g., Refs. 1,11,47). Within the framework of a cooperativity-driven glass transition, 72,73,74,75 this would imply that, for the temperature range where this process is detected (about 136 -180 K), the cooperativity length in bulk water always exceeds the pore size of about 1.2 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations